The Cello, How It Works: A Practical Guide to Cello Ownership - Pagliaro, Michael J. (Rowman & Littlefield Publishers, 2023)
This book will teach you additional information about your instrument that will help you better understand how it works, how to work it, care for it, and how to be a more knowledgeable cellist.